Jurisdiction in the Private International Law of the United States - Carl, Beverly May (1986)
The paper analyzes U.S. jurisdiction, highlighting how courts assume jurisdiction in disputes involving citizens or entities of other countries. In the U.S. system, jurisdiction depends on the State where the dispute occurs, which often requires the intervention of courts in different States or countries. In this regard, the two classic methods of securing jurisdiction are explained: on the one hand, “in personam” jurisdiction, which refers to jurisdiction over persons; on the other, “in rem” jurisdiction, which deals with property within the state; and, as a third and developing basis, “quasi in rem” jurisdiction, used in some exceptional cases, is discussed. Finally, the importance of “due process” in ensuring fairness in trials is noted, and the doctrine of “forum non conveniens,” which allows courts to dismiss cases for convenience if another forum is more appropriate to resolve the dispute, is explored.